RELEVANSI PEMIKIRAN MUHAMMAD SYAHRUR PADA PENINGKATAN PERCERAIAN ASN DAN P3K DI KABUPATEN BLITAR SEBAGAI PEMBELAJARAN TERHADAP SANTRIWATI PONDOK PESANTREN ULIL ALBAB - bahrun, yusron hanafi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study investigates the applicability of Muhammad Syahrur's progressive Islamic thought to address the escalating divorce rates among civil servants and contract-based government employees (P3K) in Blitar Regency, Indonesia. The research aims to extract pertinent lessons from Syahrur's interpretations, particularly concerning gender roles and marital dynamics, for the female students of Ulil Albab Islamic Boarding School It employs a qualitative research methodology, analyzing Syahrur's philosophical and linguistic approaches to religious texts to reinterpret traditional views on marriage and divorce, which can contribute to a more nuanced understanding of contemporary marital challenges Specifically, this study examines how Syahrur's emphasis on gender equality and justice within Islamic frameworks can offer practical guidance for young Muslim women navigating modern societal pressures and marital complexities Furthermore, it explores how a deeper understanding of Syahrur's methodology can empower these students to critically engage with prevailing patriarchal norms that often contribute to marital instability, offering an alternative framework for fostering resilient and equitable marital relationships The findings are expected to provide insights into developing an educational curriculum that integrates Syahrur's progressive interpretations, thereby equipping santriwati with the intellectual tools to address the root causes of divorce, such as financial instability, unequal gender roles, and dysfunctional communication, prevalent in contemporary Indonesian society .